Note on the solution of random differential equations via ψ-Hilfer fractional derivative - S. Harikrishnan; Kamal Shah; Dumitru Baleanu; K. Kanagarajan (Advances in Difference Equations, 2018)
Abstract This manuscript is devoted to an investigation of the existence, uniqueness and stability of random differential equations with ψ-Hilfer fractional derivative. The concerned investigation of existence and uniqueness is obtained via the Schauder fixed point theorem and Banach contraction principle, respectively. Furthermore, for the respective solutions, some results related to different kinds of Ulam type stability including Hyers–Ulam, and generalized Hyers–Ulam, Hyers–Ulam–Rassias are obtained.